Report on Evaluation of the Rural Electrification Programme - Planning Commission (Planning Commission, 1965)
It was at the instance of the Planning Commission that the Programme Evaluation Organization undertook an evaluation of the rural electrification programme. the objectives of the enquiry, drawn up in consultation with the Planning Commission and the Central Water and Power Commission, included not only an examination of progress in the electrification of rural places and the administrative and organizational problems faced in the implementation of this programme, but also a review of some of the policy and planning issues, an analysis of costs, returns and relevant technoeconomic problems and an assessment of the impact of electricity on the village people and their economy. A rather complicated design had to be adopted for a study as comprehensive in scope as those objectives indicate. The hypotheses on which different aspects of the method of study were worked out, have been briefly stated in the introductory chapter, and further details of the design given in the appendix. Since rural electrification is a new area of study, the methodological aspects of this enquiry should be of interest to researchers intending to venture out in this field.
Programme Evaluation Organisation Planning Commission Government of India